Case Teaching and Writing: Another Connection with Practitioners. Issue 1 (1st January 2017) - Ward, Peter; Hill, Brian
Abstract: College students desire a practitioner-focused education. Case teaching and writing provide more meaningful connections with practitioners and the "real" world than traditional lecture classes. Case teaching is a teaching approach using authentic, challenging, organizational scenarios with unstructured problems requiring students to analyze situations, apply principles, and create solutions through a discussion format. Case teaching provides students with the opportunity to work from the higher-order learning levels of Bloom's Taxonomy and encourages them to challenge their existing mental models, experiment with new ideas, become engaged in the learning process, and reach higher levels of learning. Cases can be taught successfully in recreation management courses through a variety of classes, formats, and assignment expectations. Practitioners might also be involved through case competitions. A large number of cases have been developed for use in business schools that incorporate experience industry firms and organizations. Recreation professors working closely with practitioners to meet the specific learning outcome needs of a recreation management course or topic might also develop cases together. An example of writing a case with practitioner input is The Color Run case with the help of its national race director.